2019
DOI: 10.1039/c9py01393h
|View full text |Cite
|
Sign up to set email alerts
|

A solvent-less green synthetic route toward a sustainable bio-based elastomer: design, synthesis, and characterization of poly(dibutyl itaconate-co-butadiene)

Abstract: Synthesis of a novel bio-based elastomer based on bio-derived monomers by using a solvent-less synthetic strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 47 publications
1
17
0
Order By: Relevance
“…Figure S2 displays the PSA-1000 spectrum 1 H NMR integrated and assigned with identical nomenclature. According to the present results, Satoh et al [ 28 ] reported an identical assignment of proton signals for a DBI copolymer; however, other similar works report the methylene protons 1 of the main chain at δ = 1.4 [ 29 ] and 1.6 [ 30 ].…”
Section: Resultssupporting
confidence: 78%
“…Figure S2 displays the PSA-1000 spectrum 1 H NMR integrated and assigned with identical nomenclature. According to the present results, Satoh et al [ 28 ] reported an identical assignment of proton signals for a DBI copolymer; however, other similar works report the methylene protons 1 of the main chain at δ = 1.4 [ 29 ] and 1.6 [ 30 ].…”
Section: Resultssupporting
confidence: 78%
“…This problem is solved by a strategy that itaconic acid is esterified with an alcohol and the resulting itaconic ester is then copolymerized with olefins to obtain elastomers. [210][211][212][213][214][215][216][217][218][219][220][221][222] The properties of the elastomers depend, among on other parameters, on the length of the alkyl of the alcohol used. For example, the glass transition temperature of poly(di-n-alkyl itaconate-isoprene) rubber (PDAII) decreases with increasing the alkyl length.…”
Section: Bio-based Elastomers Based On Itaconic Acidmentioning
confidence: 99%
“…2 Itaconic acid can be used to prepare elastomers, plastics, coatings and adhesives. 3–9 It can be esterified with alkyl alcohols with different side-group lengths ( e.g. , methanol, ethanol and butanol) to synthesize the dialkyl itaconate.…”
Section: Introductionmentioning
confidence: 99%